Diversity of aquatic insects in water hyacinth (Eichhornia crassipes) leaf litter in aquaculture experiment ponds - Salzabila Diana; Hamdhani Hamdhani; Ristiana Eryati (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
Aquatic insects are known as insects that spend part of their lives in water. Water insects are very important for ecological systems because they are often used as indicators of pollution levels in waters. The purpose of this study was to determine the types of aquatic insects and how the level of diversity, evenness and dominance of aquatic insects in the Aquaculture Experimental Pond. Five orders and seven families of aquatic insects were found in water hyacinth leaf litter. The results of the calculation of the diversity index in water hyacinth leaf litter are in the low and medium categories, for the evenness index in the low category and for the dominance index in the low to high category.